2017
DOI: 10.1098/rstb.2016.0323
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of adult sex ratios and racial/ethnic disparities in transmission of HIV and other sexually transmitted infections in the USA

Abstract: In Black population centres in the USA, adult sex ratios (ASRs) are strongly female-biased primarily due to high male incarceration and early mortality rates. I explore the system of social determinants that shape these ASRs, and describe their apparent consequences. Evidence suggests that female-biased ASRs play a role, along with racial residential segregation, to increase mixing between core and peripheral members of sexual networks, facilitating transmission of human immunodeficiency virus and other sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 123 publications
(159 reference statements)
0
14
0
Order By: Relevance
“…We have previously shown that it is the women in female-biased areas and women of low SES who start reproducing early in this population, often without the support of a partner [11]. Because abortion is illegal in Northern Ireland, risky (unprotected) sex, which has been shown to be more common in femalebiased areas [18], might lead to early parenthood for these women more often than if abortion were legal and more easily accessible.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously shown that it is the women in female-biased areas and women of low SES who start reproducing early in this population, often without the support of a partner [11]. Because abortion is illegal in Northern Ireland, risky (unprotected) sex, which has been shown to be more common in femalebiased areas [18], might lead to early parenthood for these women more often than if abortion were legal and more easily accessible.…”
Section: Discussionmentioning
confidence: 93%
“…This research has implications for female subjective wellbeing in areas that have female biased sex ratios. For example, Similarly, sex ratios may become strongly female biased after war (Brainerd, 2017) or in communities with high male crime and incarceration (Pouget, 2017). University campuses across many countries have female biased sex ratios, and women from the these colleges are appropriately pessimistic about their dating prospects (Uecker & Regnerus, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They find evidence that present-day marital and life satisfaction are higher in areas that were more male-biased in the past. Pouget [60] explores sexual relationships, bargaining power and family outcomes in the contemporary USA. In many African -American communities, men are rare due to high rates of incarceration and mortality.…”
Section: (C) Applications Of Adult Sex Ratio Researchmentioning
confidence: 99%